Multiomics Analysis of Neuroblastoma Cells Reveals a Diversity of Malignant Transformations - Narmontė, Milda; Gibas, Povilas; Daniūnaitė, Kristina; Gordevičius, Juozas; Kriukienė, Edita (Frontiers in Cell and Developmental Biology, 2021)
Neuroblastoma (NB) is a pediatric cancer of the developing sympathetic nervous system that exhibits significant variation in the stage of differentiation and cell composition of tumours. Global loss of DNA methylation and genomic 5-hydroxymethylcytosine (5hmC) is a hallmark of human cancers. Here, we used our recently developed single base resolution approaches, hmTOP-seq and uTOP-seq, for construction of 5hmC maps and identification of large partially methylated domains (PMDs) in different NB cell subpopulations. The 5hmC profiles revealed distinct signatures characteristic of different cell lineages and stages of malignant transformation of NB cells in a conventional and oxygen depleted environment, which often occurs in tumours. The analysis of the cell type-specific PMD distribution highlighted differences in global genome organization among NB cells that were ascribed to the same lineage identity by transcriptomic networks. Collectively, we demonstrated a high informativeness of the integrative epigenomic and transcriptomic research and large-scale genome structure in investigating the mechanisms that regulate cell identities and developmental stages of NB cells. Such multi-omics analysis, as compared to mutational studies, open new ways for identification of novel disease-associated features which bring prognostic and therapeutic value in treating this aggressive pediatric disease.